PERAN MEDIA POSTER DALAM PELAKSANAAN BIMBINGAN DAN KONSELING AGAMA - intan revlina revlina (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2022)
Abstract Islamic guidance and counseling is a process of guidance or assistance in which all processes are based on the teachings of the Islamic religion. In carrying out guidance, various media can be used to support guidance activities. One of the media that can be used in the guidance process is posters. Poster is a publication media consisting of writing, images or a combination of both. Posters aim to convey a certain purpose or information to the general public. The criteria for a good poster to be used in guidance are: concise slogans, clear writing, varied motifs and designs, simple, effective, presents one idea, and is colorful.